PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK DIGITAL GUNA MENINGKATKAN KESADARAN DAMPAK BULLYING TERHADAP SELF ESTEEM SISWA TINGKAT SEKOLAH DASAR - Cahyaningtias, Oktavia Annisa; Darma, Widia; Rispatiningsih, Dwi Maryani (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
One of the big mistakes in the character formation process is assuming that character formation must be taught in formal educational institutions. As a result, people outside formal educational institutions tend not to care or do not want to support the formation of this character. There are many events that shouldn't happen at school, starting from making fun of friends, clapping, calling friends by their parents' names, not being chosen when forming groups, not being invited to play or go to the canteen together, isolating, inciting, intimidation, oppression, no one is even willing to sit at the same table with the victim. The likelihood of bullying actually occurring depends on many factors including the psychological state of the bully, possible support or cooperation from other group members, and the victim's reaction. As technology develops, comics are starting to innovate, from initially being in physical book form to digital form. Using digital comics as a learning medium is one learning innovation that can be implemented. Digital comics can be a combination of text, images and learning videos that provide audio and visual simulations that increase students' enthusiasm for learning. The use of this learning media can change the learning process in the classroom. Development of Comic-Based Learning Media to Increase Awareness of the Impact of Bullying on Self Esteem using research and development methods. Research and development is a research method used to produce certain products and test the effectiveness of these products. In this research, the product that will be produced is a digital comic entitled